INDEKS PEMBANGUNAN MANUSIA INDONESIA: ANALISIS FAKTOR KETERCAPAIAN DAN REKOMENDASI: Ade Setiadi - Pengelola Jurnal CENDEKIA Jaya; Ade Setiadi (CENDEKIA Jaya, 2026)
Human Resources are crucial for a country's economic development, which can be measured using the Human Development Index (HDI). This requires supporting factors to achieve Indonesia's HDI, where the increase in HDI is not evenly distributed across all regions. The research aims to analyze factors influencing HDI achievement in Indonesia and provide recommendations for better HDI attainment. This research employs a descriptive quantitative approach, with life expectancy, expected years of schooling, and average years of schooling as independent variables, and Human Development Index (HDI) as the dependent variable. Data analysis uses multiple regression analysis based on secondary panel data (combined time series and cross-section data) across all Indonesian Provinces from 2020-2023. The research findings indicate that all three independent variables significantly partially influence the human development index, with the most significant impact from average years of schooling and the least impact from expected years of schooling. The recommendations include not only focusing on the quantity of educational facilities in high-density population areas but also improving healthcare service quality, equitable educational access in underdeveloped regions, enhancing learning quality through technology utilization, and fostering collaboration among academics, government, and community beneficiaries.